A cross-cultural pragmatic analysis of commercial advertisements in American and Vietnamese magazines - Đỗ, Thị Phương Mai (2020)
The purpose of this dissertation is to examine the use of politeness strategies, advertising appeals and the realization of politeness strategies in advertising appeals in American and Vietnamese commercial magazine advertisements. The data for this study consist of 310 magazine advertisements collected within a period of six months at the end of 2014. These advertisements are analyzed on the basis of Brown and Levinson’s (1987) politeness theory and Pollay’s (1983) advertising appeal system. The results reveal the preferences in the use of positive politeness strategies in both American and Vietnamese advertisements. Additionally, Effectiveness, Distinctive and Modern are the three most popular appeals in selected advertisements. Another similarity between American and Vietnamese magazine advertising is the realization of positive politeness strategies in Effectiveness appeal. However, there exist the differences in the use of politeness strategies and advertising appeals between American and Vietnamese advertising. At the same time, the manifestation of some politeness strategies, advertising appeals, and the realization of certain politeness strategies in advertising appeals in American advertising is different from that of Vietnamese advertising. The findings of the study, therefore, suggest that appropriate advertising strategies be employed to achieve the goal of the advertisements.